Discourses of Islamic Finance Supporting in Muslim-Friendly Tourism in the New Normal Era (Indonesia Cases) - Nugroho, Lucky; Cetin, Gurel; Meiwanto Doktoralina, Caturida (KnE Social Sciences, 2023)
This conceptual paper analyzes how to develop Muslim-friendly tourism in Indonesia in the new era to increase the number of Muslim tourists. Furthermore, the method is qualitatively based on research questions: (i) What is the government’s strategy to develop Islamic finance in Indonesia? (ii) What is Indonesia’s strategy for developing halal products and services? (iii) What is the strategy for developing Islamic finance to strengthen Muslim-friendly tourism and the creative economy?. The result showed that the existence of Islamic finance and digital ecosystems are very much needed. Therefore, the implication of this conceptual paper is to provide input and information to stakeholders who have the authority to develop Muslim-friendly tourism in Indonesia; and that there is a need for collaboration and synergy between parties, especially in the Islamic finance industry. Keywords: digital era, finance, halal tourism, post-pandemic, supply chain